The Theory-Practice Gap in Capital Budgeting: Empirical Study from Croatia - Dina KORENT; Dunja VISNJIC (Communications of International Proceedings, 2023)
The aim of this paper is to investigate, determine and compare the (non-)existence of the theory-practice gap of capital budgeting of medium-sized and large companies in Croatia. Empirical research was conducted using a questionnaire that was sent to all mentioned companies listed in the databases of the Financial Agency (2,030). The response rate was 5.12%. In addition to general scientific methods, descriptive and inferential statistics methods are used. The results indicate that the companies in question predominantly use capital budgeting and risk assessment methods, with emphasis on sophisticated and theoretically advocated NPV and IRR methods, however, in combination with inferior non-DCF and other methods, with dominant use of PBP method, and with emphasis on simulation method, sensitivity analysis and scenario analysis. Therefore, the gap between theory and practice exists in the context of the present predominance of using the PBP method and insufficiently extensive integration and spread of theory in practice.
Keywords: capital budgeting; theory; practice; gap; Croatia